The Touch Book : The Five Senses - Jane Belk Moncure (U.S.A Childrens Books)
Fingers are made for touching fuzzy, cold, warm, sticky, lumpy, furry, rough, smooth, soft, hard, slippery, and prickly things
Keywords: PY-UOI-Who We Are